Sexual dimorphism in odontometric parameters using cone beam CT: a systematic review - M. A. Ajmal; Tina S. Roberts; Khaled R. Beshtawi; A. C. Raj; N. C. Sandeepa (Head & Face Medicine, 2023)
Abstract Objective To determine whether odontometric parameters using cone beam computed tomography (CBCT) would aid in sex estimation by assessing sexual dimorphism of odontometric parameters. Material and methods The focused question was whether there is sexual dimorphism in linear and volumetric odontometric parameters when assessed using CBCT. The preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines were followed to conduct a systematic search until June 2022 in all major databases. Data were extracted regarding the population, size of the sample, age range, teeth analyzed, linear or volumetric measurements, accuracy, and conclusion. The quality of included studies was assessed using (Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. Results Out of the 3761 studies identified, twenty-nine full-text articles were assessed for eligibility. Finally, twenty-three articles (4215 participants) that provided data on odontometrics using CBCT were included in this systematic review. The odontological sex estimation were assessed either linear measurements (n = 13) or volumetric measurements (n = 8) or both (n = 2). Canines were analysed in maximum number of reports (n = 14), followed by incisors (n = 11), molars(n = 10) and premolars(n = 6). Most of the reports (n = 18) confirmed the existence of sexual dimorphism in odontometric parameters when assessed using CBCT. No significant differences in odontometrics between the sexes were noted in some reports (n = 5). The accuracy of sex estimation was assessed in eight investigations, which ranged from 47.8 to 92.3%. Conclusions Odontometrics of human permanent dentition using CBCT exhibit a certain degree of sexual dimorphism. Both linear and volumetric measurements of teeth can aid sex estimation.